NILAI PO SAPO ESEMPAY (KESETIAKAWANAN) DAN SOKKLA (KEAGAMAAN) DALAM PENENTUAN HARGA JUAL ROTI DAN KUE DI MADURA: SEBUAH STUDI FENOMADUROLOGI - Rusmiati Ningsih; Robiatul Robiatul Auliyah; Achdiar Redy Setiawan (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
This research seeks to uncover the practice of selling bread and cakes in Madura. This research using qualitative methods in the process of discovery the answers, and also phenomadurological approach in the process of analysis the extending about awareness of